Bactericidal effect of normal swine sera on Treponema hyodysenteriae. - Joens, L A (1986)
Treponema hyodysenteriae was incubated in 20% normal swine sera (NSS) at 37 degrees C for 4 h, and viability was determined by a plate dilution method. NSS was bactericidal for nonpathogenic T. innocens and avirulent T. hyodysenteriae, but not for virulent T. hyodysenteriae isolates. Heat inactivation at 56 degrees C for 30 min, treatment with EDTA or EGTA [ethylene glycol-bis(beta-aminoethyl ether)-N,N-tetraacetic acid], or removal of immunoglobulin M eliminated the bactericidal activity of NSS. However, removal of the alternate complement pathway with 10 mg of bentonite per ml did not remove bactericidal activity of NSS. Incubation of virulent isolates of T. hyodysenteriae in the presence of specific antisera plus NSS resulted in bactericidal activity. These data suggest that complement and natural antibody may be involved in protecting the host from T. innocens or avirulent T. hyodysenteriae and that T. hyodysenteriae antibody plus complement are involved in protecting convalescent pigs from re-exposure to swine dysentery.